Prevención de infecciones asociadas a la atención sanitaria en centro quirúrgico: revisión sistemática - García Alarcón, Marco Vinicio (2025)
Introduction: Healthcare-Associated Infections (HAIs) represent a major public health problem, with economic and social implications, and pose a challenge for healthcare institutions and medical staff. In hospitals, preventing these infections, especially in operating rooms, is crucial to ensure the safety and well-being of patients undergoing surgery. Objective: To determine which are the measures to prevent Healthcare-Associated Infections in surgical centers. Methodology: This study has a descriptive and explanatory scope because it will describe the different interventions of the nursing staff, using the PICO question and then the PRISMA methodology in different databases. Results: It was established that adequate management and nursing care are essential to reduce infections in operating rooms. Investment in training and protocols is justified, especially to protect vulnerable groups, and safety issues are identified, highlighting the need to improve staff training and supervision. Conclusion: Infection prevention in operating rooms is crucial and depends on effective nursing management. It is essential to protect vulnerable groups and address safety issues, such as antibiotic resistance, through staff training and rigorous protocols to ensure safe care.